2011
DOI: 10.1007/s12288-011-0072-4
|View full text |Cite
|
Sign up to set email alerts
|

Uric Acid as a Potential Biomarker of Pulmonary Arterial Hypertension in Patients with Sickle Cell Disease

Abstract: Serum uric acid (UA) is emerging as a strong and independent marker for pulmonary arterial hypertension (PAH). PAH is well recognized as a life threatening complication of sickle cell disease (SCD). However, the association between UA and PAH in SCD is unknown. We reviewed electronic medical records (EMR) of 559 consecutive adult SCD patients from Kings County Hospital Center (KCHC) between January 2005 and February 2010. Patients (n = 96) with measurement of UA in close temporal proximity to the transthoracic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Two studies reported that UA in patients with PAH than in healthy subjects, which was coherent with the present results.…”
Section: Discussionsupporting
confidence: 93%
“…Two studies reported that UA in patients with PAH than in healthy subjects, which was coherent with the present results.…”
Section: Discussionsupporting
confidence: 93%
“…Hyperuricemia in SCA patients has been associated with leg ulcers and pulmonary hypertension [24, 25]. In non-SCA pediatric and adult populations, hyperuricemia has been associated with a decrease in eGFR and progression to CKD [17, 39-41].…”
Section: Discussionmentioning
confidence: 99%
“…Hyperuricemia has been associated with hypertension and cardiovascular events in other diseases but, despite the high prevalence of hyperuricemia in SCA, the association of hyperuricemia and sickle cell nephropathy has not been explored [18, 19]. Hyperuricemia has been associated with leg ulcers and pulmonary hypertension in SCA [23-25]. …”
Section: Introductionmentioning
confidence: 99%
“…The particular contributions of all these factors are yet to be established. However, some of them have been already reported as promising biomarkers associated with PAH (74, 111, 137, 145). It, therefore, follows that further validation of such biomarkers that could be routinely screened, at least in the PAH patient's family members or in high-risk patients, could help to identify this deadly disease at the early, curable stage.…”
Section: Vascular Damage and Inflammationmentioning
confidence: 99%